Audiologic, surgical and subjective outcomes of active transcutaneous bone conduction implant system (Bonebridge). (2nd December 2019) - Oh, Se-Joon; Goh, Eui-Kyung; Choi, Sung-Won; Lee, Seokhwan; Lee, Hyun-Min; Lee, Il-Woo; Kong, Soo-Keun
Abstract: Objective: Our objective was to evaluate the surgical restrictions, audiologic benefits and satisfaction from using an active transcutaneous bone conduction device (BCD), Bonebridge ® (BB) in patients with mixed/conductive hearing loss (MCHL) or single-sided deafness (SSD). Design: A retrospective review from all patients who underwent BB surgery at the Pusan National University Hospital from 2015 to 2017 for SSD or MCHL was performed. Study sample: Twenty-two patients with SSD and five with MCHL had a BB implanted and analysed. Results: Complete transmastoid implantation of the device was possible for all patients with an intact canal wall (ICW), using lifts if necessary. The overall functional hearing gain (FHG) in SSD and MCHL was 31.4 and 37.6 dB, respectively. The mean percentage of speech recognition in a quiet was 81% ( vs. 11% unaided) for MCHL group and 82% ( vs. 29% unaided) for SSD group. Mean speech recognition scores in noise improved significantly under various signal-to-noise ratio (SNR) for both groups. Questionnaires showed overall improvement, and there was no significant difference between the two groups. Conclusions: The BB provides improved functional gain, and there were no limitations during surgery despite the large device. Both MCHL and SSD group had benefit and improved quality of life with BB.